Omnibus Law and the Challenges of the Indonesian Agricultural Sector: an Islamic Perspective - Rasyid, Tengku Harunur; Kusumawaty, Yeni (Perhimpunan Intelektual Muslim Indonesia, 2022)
In late 2020, the Indonesian Parliament enacted the Job Creation Law, known as the